Optimize the position of distributed generations in distribution grid by using improved loss sensitivity factor - Phan, Dinh Chung; Luu, Ngoc An (Institute of Advanced Engineering and Science, 2024)
This research proposed a method to determine the optimal position of distributed generations in a distribution grid. The method is improved from the loss sensitivity factor method. An algorithm is developed to determine both the position and size of distributed generations. This algorithm is validated via IEEE 33 bus distribution grid in two cases of distributed generation size including unknown size and constant size. The results were analyzed and compared to other previous algorithms including loss sensitivity factor-based algorithm and other algorithms. Results indicated the optimal position of each distributed generation to minimize the power loss. Results also indicated that with the proposed algorithm, the loss reduction rate (LRR) is the highest in comparison to that with other previous algorithms.